Does the mortality salience effect on worldview defence depend on the cultural orientation of Chinese people?. (28th December 2018) - Zeng, Taoran; Tse, Chi‐Shing
Abstract : According to the terror management theory, people tend to favour their worldview and in‐group members after being reminded of death (i.e., mortality salience [MS] effect). However, inconsistent findings of the MS effect were found among Chinese people. In the present study, we examined the MS effect with Chinese samples and tested whether the effect would depend on participants' cultural orientation and relational self‐esteem. In Studies 1 ( N  = 227) and 2 ( N  = 221), we examined the roles of participants' cultural orientations and relational self‐esteem in their evaluations on moral transgression and/or perceived regard from people around after being primed with mortality (vs. dental pain) salience. We obtained the interaction effects of mortality salience, cultural orientations, and relational self‐esteem. The implications of these results are discussed in the context of Chinese culture.